Heme Binding Biguanides Target Cytochrome P450-Dependent Cancer Cell Mitochondria. Issue 10 (19th October 2017) - Guo, Zhijun; Sevrioukova, Irina F.; Denisov, Ilia G.; Zhang, Xia; Chiu, Ting-Lan; Thomas, Dafydd G.; Hanse, Eric A.; Cuellar, Rebecca A.D.; Grinkova, Yelena V.; Langenfeld, Vanessa Wankhede; Swedien, Daniel S.; Stamschror, Justin D.; et al.
Summary: The mechanisms by which cancer cell-intrinsic CYP monooxygenases promote tumor progression are largely unknown. CYP3A4 was unexpectedly associated with breast cancer mitochondria and synthesized arachidonic acid (AA)-derived epoxyeicosatrienoic acids (EETs), which promoted the electron transport chain/respiration and inhibited AMPKα. CYP3A4 knockdown activated AMPKα, promoted autophagy, and prevented mammary tumor formation. The diabetes drug metformin inhibited CYP3A4-mediated EET biosynthesis and depleted cancer cell-intrinsic EETs. Metformin bound to the active-site heme of CYP3A4 in a co-crystal structure, establishing CYP3A4 as a biguanide target. Structure-based design led to discovery of N1-hexyl-N5-benzyl-biguanide (HBB), which bound to the CYP3A4 heme with higher affinity than metformin. HBB potently and specifically inhibited CYP3A4 AA epoxygenase activity. HBB also inhibited growth of established ER + mammary tumors and suppressed intratumoral mTOR. CYP3A4 AA epoxygenase inhibition by biguanides thus demonstrates convergence between eicosanoid activity in mitochondria and biguanide action in cancer, opening a new avenue for cancer drug discovery. Graphical Abstract: Highlights: CYP3A4 is an arachidonic acid (AA) epoxygenase required for breast tumor formation CYP3A4 suppresses autophagy in breast cancer, in part, by inhibiting AMPK activation CYP3A4 AA epoxygenase activity promotes the mitochondrial electron transport chain Metformin inhibits breast cancer, in part, by inhibiting CYP3A4 AA epoxygenase activity Abstract : Guo et al. discover inhibition of CYP3A4 AA epoxygenase by biguanides, thereby demonstrating convergence between eicosanoid activity in mitochondria and biguanide action in cancer, opening a new avenue for cancer drug discovery.